Future Socio-Political Scenarios for Aquatic Resources in Europe: An Operationalized Framework for Aquaculture Projections - Kreiss, Cornelia M.; Papathanasopoulou, Eleni; Hamon, Katell G.; Pinnegar, John K.; Rybicki, Sandra; Micallef, Giulia; Tabeau, Andrzej; Cubillo, Alhambra M.; Peck, Myron A. (Frontiers in Marine Science, 2020)
Climate-driven changes in aquatic environments have already started to affect the European aquaculture sector’s most commercially important finfish and shellfish species. In addition to changes in water quality and temperature that can directly influence fish production by altering health status, growth performance and/or feed conversion, the aquaculture sector also faces an uncertain future in terms of production costs and returns. For example, the availability of key ingredients for fish feeds (proteins, omega-3 fatty acids) will not only depend on future changes in climate, but also on social and political factors, thereby influencing feed costs. The future cost of energy, another main expenditure for fish farms, will also depend on various factors. Finally, marketing options and subsidies will have major impacts on future aquaculture profitability. Based on the framework of four socio-political scenarios developed in the EU H2020 project CERES (Climate change and European aquatic RESources), we defined how these key factors for the aquaculture sector could change in the future. We then apply these scenarios to make projections of how climate change and societal and economic trends influence the mid-century (2050) profitability of European aquaculture. We used an established benchmarking approach to contrast present-day and future economic performance of “typical farms” in selected European production regions under each of the scenarios termed “World Markets”, “National Enterprise”, “Global Sustainability” and “Local Stewardship". These scenarios were based partly on IPCC Special Report on Emissions Scenarios framework and their Representative Concentration Pathways (RCPs) and the widely used Shared Socioeconomic Pathways (SSPs). Together, these scenarios contrast local versus international emphasis on decision making, more versus less severe environmental change, and different consequences for producers due to future commodity prices, cash returns and costs. The mid-century profitability of the typical farms was most sensitive to the future development of feed costs, price trends of returns and marketing options as opposed to the direct effect of climate-driven changes in the environment. These results can inform adaptation planning by the European aquaculture sector. Moreover, applying consistent scenarios including societal and economic dimensions, facilitates regional to global comparisons of adaptation advice both within and across Blue Growth sectors.